Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Tax Avoidance - Naurah Balqis Hafsari; Ludigdo, Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to assess and elucidate the effects of corporate social responsibility (CSR) disclosure and good corporate governance (GCG) on tax avoidance. As the corporate governance was proxied by institutional ownership, independent commissioners, and board of directors, the social and environmental responsibility was measured using the 2021 GRI Universal Standard and POJK number 51/POJK.03/2017. Through purposive sampling, 30 energy companies listed in the Indonesia Stock Exchange during the 2021-2023 period were selected as a result, 90 samples were obtained. The results of the data analysis using multiple linear regression suggest that CSR and GCG simultaneously influence tax avoidance, that CSR positively affects tax avoidance, that institutional ownership and number of board of directors positively influence tax avoidance, and that independent commissioners have no impact on tax avoidance. The findings of this research confirm the Agency Theory, which implies that improvements in corporate governance help overcome agency problems, and the Stakeholder Theory, which states that companies need to prioritize the interests of all stakeholders in order to achieve long-term success.